Epidemiological revision of high fertility behaviors among mothers in Mosul city, Iraq - Aljawadi, Asma A.; Al-Ridhwany, Hajir H.; Abduljawad, Muthanna S. (Zanco Journal of Medical Sciences (ZJMS), 2019)
Background and objective: Collective high fertility behaviors is a term that refers to mothers who had got married during their teenage and having parity of five or more living children with less than 24 months apart. The present study aimed to estimate the prevalence of collective high fertility behaviors among mothers in Mosul city, Iraq. Methods: A cross-sectional study was carried out using a multi-stage stratified sampling method. Inclusion criteria included mothers in child-bearing age who had at least two living children. The required data were collected by filling an especially structured questionnaire in the eligible primary health care centers over a period of ten months, from April, 1st 2011 to the end of January 2012. Results: Among 1302 participants, the prevalence of high fertility behaviors was 17.7% within all age groups. The prevalence was significantly higher among Muslim, low social classes (P ˂0.001), nuclear family structure (P ˂0.001), consanguineous marriage (P ˂0.001) and low educated mothers and husbands (P ˂0.001). Conclusion: The study found that collective high fertility behaviors are prevalent among almost two out of ten mothers of all age groups in Mosul city. Thus, effective engagement of all human resources is recommended for constructing healthy fertility behaviors and confirming the non-reproductive role of women.